Using Dates Leaves Midribs to Prepare Hierarchical Structures Incorporating Porous Carbon and Zeolite A Composites for Cesium137Cs Ion Exchange (Baghdad Science Journal, 2020)
This study synthesized zeolite 4A, and hierarchical composite structure consisting of zeolite 4A- carbon were successfully prepared. Hydrothermal method was used to grow a layer of zeolite 4A over porous carbon surfaces to enhance mass transfer and increase surface area of zeolite. The products then were used to remove radioactive cesium137Cs from liquid wastewater. Iraqi dates leaves midribs (DM) were used as locally available agricultural waste to prepare low- cost porous carbon, using carbonization method in tubular furnace at 900C for two hours. Hierarchical porous structures including zeolite are prepared by mechanically activating the carbon surface via Ultrasonicating nanoparticles suspension of ground zeolite type 4A.For preparing nanoparticles suspension, commercial zeolite has been milled using 0.3-0.4 mm diameter glass balls as grinding media. Nanoparticles of zeolite 4A acting as seeding (nucleation centers) increase the crystallization of amorphous aluminosilica gel on modification carbon surface. The products of the syntheses zeolite 4A and the hierarchal composite materials (DMZ) were characterized using Scanning Electron Microscopy (SEM), X-ray diffraction (XRD), Nitrogen sorption (BET) and Energy dispersive X-ray spectrometer (EDX) to check the morphology, structure, surface area, and the chemical composition respectively. The products were used to treat radioactive wastewater contaminated with radioactive cesium 137Cs collected from destroyed building of the Radiochemistry Laboratories (RCL) in AL-Tuwaitha Nuclear Site. The activity concentration for the contamination water pre and after the treatment were measured using gamma spectroscopy system supplied with a high purity germanium detector (HPGe) with 60% relative efficiency. The results showed that the radioactivity concentration after the treatment process decreased significantly from 4800 Bq/L to 186 and Bq/L,121 Bq/L using 0.045 gm from synthesized zeolite 4A and DMZ respectively.